Biopetrol synthesized from rubber seed oil through heterogeneous catalytic cracking using kaolinite as catalyst - Siti Hajar, Abdul Halim (2010)
Biopetrol is defined as fuel which has the same characteristics with commercial petrol in term of its molecular formula. Depleting in finite fossil fuel and the valuable fatty acid loss by disposal to environment are the problematic reasons that the biopetrol should be synthesize from fatty acid. The purpose of this study is to synthesize isooctane (biopetrol) from rubber seed oil via catalytic cracking using kaolinite as catalyst. Soxhlet extraction method is used to extract the fatty acid from blended rubber seeds kernel using hexane as solvent. The catalytic cracking process is used to synthesize isooctane from distillate fatty acid and it was conducted at 98°C for 2 hours. 20 g mass of catalyst is used. The effect of different dilution of samples at 1%, 5%, 10% and 20% are studied over the concentration of isooctane. Gas chromatography is used for the qualitative and quantitative analysis of the samples. Backward calculation is applied to calculate the actual concentration of isooctane in the distilled rubber seed oil. The result showed that isooctane concentration is around 88%-108%. The factor of random reaction in cracking process, small quantity of sample, the unmodified axis peak area of impurities and also the factor of contamination effect the result obtained. This research proved that isooctane can be synthesized from rubber seed oil.